MOOC’s benefits for higher education students during the academic emergency due to Covid-19 (Práxis Educativa, 2021)
The academic contingency due to covid-19 caused an acceleration in the sum of online education initiatives in higher education, including MOOC (Massive Open Online Course). This article documents a research exercise on the experience of a Mexican public university, which, during the pandemic, incorporated into its teaching proposal the possibility of its students taking some MOOC. The qualitative study, based on content analysis, aimed to identify, from the students' point of view, the benefits of participating in this type of learning experiences. The results indicate a set of benefits integrated into six categories: academic development, professional development, personal development and motivation, flexibility, internationalization and academic continuity. The conclusion is aimed at confirming the existence of benefits and that within them there are particularities associated with the academic contingency scenario.Keywords: MOOC. Covid-19. Higher education.